2021
DOI: 10.1111/risa.13801
|View full text |Cite
|
Sign up to set email alerts
|

It's Politics, Isn't It? Investigating Direct and Indirect Influences of Political Orientation on Risk Perception of COVID‐19

Abstract: Public response to the COVID‐19 pandemic provides a unique opportunity to study risk perception in relation to political orientation. We tested a risk perception model of how political orientation influences risk perception of an emerging infectious disease and how it moderates other influences. Two nationwide online surveys in South Korea (N = 2,000) revealed that conservatives showed a higher risk perception regarding an emerging infectious disease, and political orientation can even moderate the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 71 publications
(94 reference statements)
4
20
1
Order By: Relevance
“…The massively developing social network phenomenon has become the main dissemination platform for COVID-19 information and has attracted significant attention from emergency management agencies. One survey showed that the frequency of media use was positively associated with higher RP ( 13 ). Social media has become an important channel by which public could seek and share a staggering amount of health-related information and more so during the outbreak of COVID-19 ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The massively developing social network phenomenon has become the main dissemination platform for COVID-19 information and has attracted significant attention from emergency management agencies. One survey showed that the frequency of media use was positively associated with higher RP ( 13 ). Social media has become an important channel by which public could seek and share a staggering amount of health-related information and more so during the outbreak of COVID-19 ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been conducted to analyze the preventive behavior of COVID-19 by applying EPPM in Europe [ 7 ], the United States [ 19 ], Canada [ 23 ], and Asia [ 19 , 21 ], to the best of our knowledge, this study is the first to investigate social distancing participation factors through the EPPM framework in Korea; specifically, this is evaluated as successfully coping with the spread of COVID-19 [ 36 ]. This study demonstrates that EPPM can explain an individual’s behavior in coping with infectious diseases as an emotional and cognitive dynamic process, even in culturally and politically different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The sociodemographic variables included in the analysis were sex (0 = men, 1 = women), age (in years), education (0 = high school or below, 1 = college or above), monthly household equivalence income (values ranging from 1 (under 1,724 US dollars(USD)) to 4 (5,143 USD or above), and employment status (0 = unemployed, 1 = employed)). People with chronic diseases are highly vulnerable to COVID-19 infection [ 34 ]; research suggests that an individual’s health status is associated with performing COVID-19 preventive measures, COVID-19 pandemic fear, and risk perception [ 35 , 36 ]. Therefore, we asked participants about their health status.…”
Section: Methodsmentioning
confidence: 99%
“…As in the mediation analyses reported previously, political orientation would be expected to impact individuals’ decision making in the context of COVID-19 preventive behaviors. As an illustration, political orientation has been shown to moderate effects of perceived determining factors like catastrophic potential, dread, and moral nature on risk perceptions, a social cognition construct ( Ju & You, 2022 ). However, there has been few investigations examining political orientation as a moderator within social cognition models, particularly its role as a moderator of the intention-behavior relationship.…”
Section: Future Directionsmentioning
confidence: 99%